Identifikasi Morfologi dan Molekuler Tanaman Salak di Kecamatan Tanah Grogot Kabupaten Paser Kalimantan Timur - Noor, Sri Maulidah; Effendi, Hamka (Sekolah Tinggi Pertanian Kutai Timur, 2022)
Salak is a tropical plant native to Indonesia whose fruit is liked by the public and has good prospects for cultivation. The development of salak in Padang Pangrapat Village, Paser Regency began in 1994, with seeds originating from Central Java so it is better known as